2017
DOI: 10.1097/md.0000000000009214
|View full text |Cite
|
Sign up to set email alerts
|

Pipkin type III femoral head fracture–dislocation combined with complicated acetabular fracture

Abstract: Rationale:Pipkin III fracture, which is characterized by high risk of avascular necrosis of the femoral head, is extremely rare. It is more difficult to treat and has a worse prognosis when accompanied with severe acetabular fractures. Few studies show that both Pipkin type III femoral head fracture–dislocation and complicated acetabular fracture presented in one patient.Patient concerns:A 34-year-old male suffered a terrible traffic accident with a serious damage to the left side when he was sitting in the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Almost all previous studies showed that these fractures are usually due to high-energy trauma, as in this study [ 6 , 8 , 9 ]. Usually, type III Pipkin’s fractures occurred when the hip is in <60 degrees of flexion, although the patient was not sure about the position of the limb in our study [ 7 ].…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Almost all previous studies showed that these fractures are usually due to high-energy trauma, as in this study [ 6 , 8 , 9 ]. Usually, type III Pipkin’s fractures occurred when the hip is in <60 degrees of flexion, although the patient was not sure about the position of the limb in our study [ 7 ].…”
Section: Discussionsupporting
confidence: 55%
“…Zhao et al [ 6 ] reported a case of type III Pipkin’s fracture with an acetabular fracture in a 34-year male. This patient had a satisfactory outcome after osteosynthesis through anterior and posterior approach after 1 year of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the presence of avascular necrosis of the femoral head, associated complications in using screw xation can only be avoided and reduced by improving the surgical technique applied. Current surgical approaches for femoral head fractures vary and include the medial approach (Ludloff approach) and the anterior approach (Smith Petersen approach), the antero-medial fenestration approach, the Watson-Jones Approach, the lateral approach and the Kocher-Langenbeck approach [13][14][15][16]. Despite these options, it remains a challenge to easily expose the femoral head and complete the reduction and xation under direct vision.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of this injury increased in these recent years due to improved resuscitation, which led to increased survival of the severely injured patients [3]. As poor functional outcomes were associated with conservative treatment of femoral head fractures, surgical treatment indications became wider [3, 7, 8]. Femoral head fractures are known to be frequently associated with femoral neck fractures, acetabular fractures, sciatic nerve neurapraxia and knee ligamentous lesions as per the mechanism of the initial injury [5, 9, 10].…”
Section: Introductionmentioning
confidence: 99%